Concept for Embedded Primary Care Pharmacist Practitioners (PCPPs): A Disruptive Value-Proposition - George E. MacKinnon (MDPI AG, 2020)
The work environments and expectations for the daily activities of primary care physicians are daunting and often include spending a significant amount of time related to chronic care management with complex medication regimens, medication reconciliation, and the documentation within the electronic medical record (EMR) of these medication related issues [...]